Advances in small molecule selective ligands for heteromeric nicotinic acetylcholine receptors - Carlo Matera; Claudio Papotto; Clelia Dallanoce; Marco De Amici (Elsevier, 2023)
The study of nicotinic acetylcholine receptors (nAChRs) has significantly progressed in the last decade, due to a) the improved techniques available for structural studies; b) the identification of ligands interacting at orthosteric and allosteric recognition sites on the nAChR proteins, able to tune channel conformational states; c) the better functional characterization of receptor subtypes/subunits and their therapeutic potential; d) the availability of novel pharmacological agents able to activate or block nicotinic-mediated cholinergic responses with subtype or stoichiometry selectivity. The copious literature on nAChRs is related to the pharmacological profile of new, promising subtype selective derivatives as well as the encouraging preclinical and early clinical evaluation of known ligands. However, recently approved therapeutic derivatives are still missing, and examples of ligands discontinued in advanced CNS clinical trials include drug candidates acting at both neuronal homomeric and heteromeric receptors. In this review, we have selected heteromeric nAChRs as the target and comment on literature reports of the past five years dealing with the discovery of new small molecule ligands or the advanced pharmacological/preclinical investigation of more promising compounds. The results obtained with bifunctional nicotinic ligands and a light-activated ligand as well as the applications of promising radiopharmaceuticals for heteromeric subtypes are also discussed.